2021
DOI: 10.22271/plants.2021.v9.i4a.1313
|View full text |Cite
|
Sign up to set email alerts
|

GC-FID phytochemical analysis of selected antidiabetic herbal preparations sold in Onitsha metropolis, Anambra state, Nigeria

Abstract: Diabetes has become one of the world's most serious public health problems. The importance of plant extracts in diabetes management is widely acknowledged. This study was designed to determine the phytochemical compositions of the selected herbal preparations, which is used for treatment of Diabetes in Nigeria. Standard method was employed and gas chromatography-flame ionization detector (GC-FID) instrument used for the analysis and quantification of phytochemicals present in the samples. The analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Ojukwu et al 35 . As 15 mL ethanol and 10 mL 50% w/v KOH was added to a test tube containing one (1 g) of sample and the test tube was allowed to sit in a water bath at 60°C for 1 hr.…”
Section: Extraction Of Chemical Constituents: Extraction Of Chemical ...mentioning
confidence: 99%
“…Ojukwu et al 35 . As 15 mL ethanol and 10 mL 50% w/v KOH was added to a test tube containing one (1 g) of sample and the test tube was allowed to sit in a water bath at 60°C for 1 hr.…”
Section: Extraction Of Chemical Constituents: Extraction Of Chemical ...mentioning
confidence: 99%
“…Tannins have been also reported to possess antibacterial activity 18 . Sparteine is a quinoline alkaloid that possesses antimicrobial and antimalarial properties and it has been reported that both proanthocynin and spartein have antibacterial activity 19 . Sparteine has been studied to possess antimicrobial activity 20 .…”
Section: Antioxidant Activitymentioning
confidence: 99%